2019
DOI: 10.1101/738658
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single Cell Transcriptional Signatures of the Human Placenta in Term and Preterm Parturition

Abstract: 1More than 135 million births occur each year; yet, the molecular underpinnings of human 2 parturition in gestational tissues, and in particular the placenta, are still poorly understood. The 3 placenta is a complex heterogeneous organ including cells of both maternal and fetal origin, and 4 insults that disrupt the maternal-fetal dialogue could result in adverse pregnancy outcomes such as 5 preterm birth. There is limited knowledge of the cell type composition and transcriptional activity 6 of the placenta an… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
54
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(63 citation statements)
references
References 75 publications
8
54
1
Order By: Relevance
“…15 Others have used scRNAseq to define novel cell types and transcriptional signatures unique to parturition at term compared to preterm. 16 Cord blood collected from the umbilical cord after birth also provides a unique opportunity to characterize the signals being passed from mother to baby via the placenta to understand changes that occur in the fetus. Mass cytometry (CyTOF) is a powerful single-cell immunophenotyping technique and, in combination with unbiased computational clustering tools, can be used to characterize immune cell populations and their dynamics.…”
Section: While Studying In Utero Development Remains Challenging Newmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Others have used scRNAseq to define novel cell types and transcriptional signatures unique to parturition at term compared to preterm. 16 Cord blood collected from the umbilical cord after birth also provides a unique opportunity to characterize the signals being passed from mother to baby via the placenta to understand changes that occur in the fetus. Mass cytometry (CyTOF) is a powerful single-cell immunophenotyping technique and, in combination with unbiased computational clustering tools, can be used to characterize immune cell populations and their dynamics.…”
Section: While Studying In Utero Development Remains Challenging Newmentioning
confidence: 99%
“…19 Thus, mass cytometry is a versatile technology which has the power to advance our knowledge and understanding of the intricacies of immunity. Combining advanced technologies that generate complementary datasets measuring cellular identify by cytometry 19,39 and transcriptional activation, as with scRNAseq, 15,16 should be a priority to move the field of fetomaternal immunity forward in the next decade.…”
Section: F I G U R Ementioning
confidence: 99%
“…The decidual immune cells at the maternal-fetal interface are mainly composed of natural killer (NK) cells, macrophages, T cells, and a variety of minority cell types (e.g., dendritic cells, NKT cells, etc.) 5 , and their proportion changes with gestational age 6 . Decidual NK (dNK) cells represent the largest population, comprising about 50-70% of the maternal immune cells during the first trimester of pregnancy 7 .…”
Section: Introductionmentioning
confidence: 99%
“…A number of recent studies have employed single-cell RNA sequencing (scRNA-seq) technology to interrogate the cellular composition and inter-cellular communication events that occur at the maternal-fetal interface 6,[21][22][23][24] . Building from these seminal studies of global cell types, subsequent focus studies of immune cell subsets have been conducted for normal decidua [25][26][27] .…”
Section: Introductionmentioning
confidence: 99%
“…Single‐cell transcriptomic data from a first‐trimester placenta demonstrated that ACE2 is highly expressed on placental cells including extravillous trophoblasts, villous cytotrophoblasts and syncytiotrophoblasts (STBs), decidual stromal cells, and fetal endothelial cells. However, this is contested by a recent paper using single‐cell RNA sequence analyses of the placenta, and new single‐cell/nuclei RNA‐sequencing data, suggesting that there is negligible co‐expression of ACE2 and TMPRSS2 in trophoblasts as well as in third‐trimester chorioamniotic membranes 48,49 . TMPRSS2 has been reported to be expressed on all three trophoblast cell types 50 .…”
Section: Introductionmentioning
confidence: 99%